Pelatihan Pembuatan Produk Simple Sirup dari Bunga Telang (Clitoria ternatea L.) di Desa Situnggaling, Kecamatan Merek, Kabupaten Karo - Efrida Pima Sari Tambunan; Soraya Saputri; Rika Rahmawati Situmorang; Syahnur Fadillah Azmi; Mahfuza Delila Harahap; Putri Fazrisina (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase the ability and creativity of the people of Situnggaling Village, Brand District, Karo Regency, in utilizing the potential of the surrounding nature in the form of telang flowers (Clitoria ternatea L.) through training in making simple syrup products. This training was attended by 34 participants consisting of housewives and village teenagers. The implementation method includes socialization of the benefits of telang flowers, syrup making demonstrations, as well as technical assistance in packaging and marketing strategies. Participants were also given an understanding of hygiene standards, the right dosage of ingredients, natural dyeing techniques, and product storage procedures to have a longer shelf life. In addition to the production aspect, this activity also discussed the economic potential of telang flower syrup products as a commodity for MSMEs, including the calculation of production costs and marketing opportunities through social media. The results showed a significant increase in participants' knowledge about the economic value and health benefits of telang flowers, as well as their ability to produce syrup independently. This activity is expected to be the first step in empowering the local potential-based economy and encouraging the formation of new sustainable home businesses in Situnggaling Village.